2014
DOI: 10.1103/physrevb.89.045418
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier relaxation processes in TbAs nanoinclusions in GaAs measured by optical-pump THz-probe transient absorption spectroscopy

Abstract: Rare-earth materials epitaxially codeposited with III-V semiconductors form small, spherical rare-earthmonopnictide nanoparticles embedded within the III-V host. The small size of these particles (approximately 1.5 nm diameter) suggests that interesting electronic properties might emerge as a result of both confinement and surface states. However, ErAs nanoparticles do not exhibit any signs of quantum confinement or an emergent band gap, and these experimental observations are understood theoretically. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…1(a) was used to fit the low fluence data where A 0 , A 1 , and A 2 are amplitude coefficients, providing information on the percentage of carriers participating in each relaxation process, and s 0 , s 1 , and s 2 are the relaxation times for each process. Consistent with previous work on TbAs:GaAs, 15 s 0 has been assigned as relaxation into the TbAs nanoparticle, s 1 as emptying the nanoparticle, and s 2 as recombination across the InGaAs band gap. At higher fluences, the saturation of traps and neighboring states reduces the fraction of carriers participating in the fastest processes (s 0 and s 1 ) to a negligible level and double or single exponential fits are used.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…1(a) was used to fit the low fluence data where A 0 , A 1 , and A 2 are amplitude coefficients, providing information on the percentage of carriers participating in each relaxation process, and s 0 , s 1 , and s 2 are the relaxation times for each process. Consistent with previous work on TbAs:GaAs, 15 s 0 has been assigned as relaxation into the TbAs nanoparticle, s 1 as emptying the nanoparticle, and s 2 as recombination across the InGaAs band gap. At higher fluences, the saturation of traps and neighboring states reduces the fraction of carriers participating in the fastest processes (s 0 and s 1 ) to a negligible level and double or single exponential fits are used.…”
supporting
confidence: 75%
“…14 Our recent carrier dynamics study shows that TbAs nanoparticles in GaAs are saturable, in direct contrast to ErAs nanoparticles, and likely have a band gap. 15 Although TbAs nanoparticles are of interest for a variety of device applications, many details of their electronic structure in III-V semiconductors are presently unknown. In this paper we propose and systematically justify a type I heterojunction for the TbAs:GaAs system and a type II heterojunction for the TbAs:InGaAs system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that changes in carrier lifetime as a function of excitation fluence originate from trap state saturation, which can depend critically on the electronic structure of the traps. 15,16 If ErAs had a band gap and discrete states, we would expect to see evidence of a phonon bottleneck and slow carrier recombination that would result in saturation of the ErAs electronic states as increasing pump fluence increased the number of carriers populating the ErAs states. 17 The absence of any saturation in the QD PL decay time ( Figure 5) allows us to conclude that carrier relaxation within the ErAs MNPs is extremely fast, consistent with a continuous density of states in semi-metallic ErAs MNPs.…”
mentioning
confidence: 99%